SYNONYMIC RELAYIONS OF ABSTRACT WORDS (Scientific journal of the Fergana State University, 2023)
This article analyzes the  synonymic approach of abstract  words. The synonymic relationships between denotative and connotative differences were analyzed in detail. The synonymy and gradation of abstract words have been explained. Oral synonymy of abstract words has also been emphasized so that there is a tendency of expression of complicated abstract essences in speech with  a clear, exact names for people, simplicity and figurative expressions.